2020
DOI: 10.1016/j.brs.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic exploration of parameters affecting evoked intracranial potentials in patients with epilepsy

Abstract: Background: Brain activity is constrained by and evolves over a network of structural and functional connections. Corticocortical evoked potentials (CCEPs) have been used to measure this connectivity and to discern brain areas involved in both brain function and disease. However, how varying stimulation parameters influences the measured CCEP across brain areas has not been well characterized. Objective: To better understand the factors that influence the amplitude of the CCEPs as well as evoked gamma-band pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 59 publications
2
48
1
Order By: Relevance
“…Many existing studies have attempted to address this by presuming a specific temporal structure in the evoked response, such as the voltage at a pre-specified timepoint post-stimulation [ 26 ]. However, as illustrated in Fig 2 and S3 Fig and reported by Kundu and colleagues [ 27 ], there is no single canonical CCEP response shape or feature, even when measuring from a single electrode.…”
Section: Discussionmentioning
confidence: 83%
“…Many existing studies have attempted to address this by presuming a specific temporal structure in the evoked response, such as the voltage at a pre-specified timepoint post-stimulation [ 26 ]. However, as illustrated in Fig 2 and S3 Fig and reported by Kundu and colleagues [ 27 ], there is no single canonical CCEP response shape or feature, even when measuring from a single electrode.…”
Section: Discussionmentioning
confidence: 83%
“…The mechanism of RNS remains poorly understood, and undoubtedly a number of factors may influence responder outcome, including location of RNS implant with respect to a patient’s seizure onset zone 37 , programming detection and stimulation parameters 13 , and interactions between RNS therapy and pharmaceutical treatments. 38 Much of the RNS parameter space has not yet been explored, and it is unclear to what extent each factor may contribute to patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A purely speculative possibility is that by maintaining a similar level of synchronizability between pre-ictal and ictal periods as shown in our broad band results, RNS responders may be better able to distribute energetic inputs to the broader epileptic network during seizures, when the device is commonly triggered for stimulation. In patients with decreased post-onset synchronizability, RNS may be less able to influence long-range plasticity mechanisms in the broader epileptic network.The mechanism of RNS remains poorly understood, and undoubtedly a number of factors may influence responder outcome, including location of RNS implant with respect to a patient's seizure onset zone37 , programming detection and stimulation parameters13 , and interactions between RNS therapy and pharmaceutical treatments 38. Much of the RNS parameter space has not yet been explored, and it is unclear to what extent each factor may contribute to patient outcome.…”
mentioning
confidence: 99%
“…Many existing studies have attempted to address this by presuming a specific temporal structure in the evoked response, such as the voltage at a pre-specified timepoint post-stimulation [25]. However, as illustrated in figures 2&S3 and reported by Kundu and colleagues [26], there is no single canonical CCEP response shape or feature, even when measuring from a single electrode.…”
Section: The Convergent Approach To Connectivitymentioning
confidence: 99%
“…Subsequent studies might vary experimental conditions with a task, medication, or property of the stimulation (current magnitude and temporal profile, or timing between pulses), and quantify signal, noise, and residual structure in the responses. For example, one could examine the effect of simply changing the amplitude of stimulation, where it has been demonstrated that different stimulation magnitudes can elicit very different morphologies [26] and examine distribution of BPCs as a function of that.…”
Section: Potential Future Applicationsmentioning
confidence: 99%